TEORI DAN TEKNIK DESENSITISASI SISTEMATIS BERBASIS ISLAM - Mutiara Cahya Noviani; Nurjannah Nurjannah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This study discusses the theory and techniques of systematic desensitization which the authors then integrate these techniques into Islamic-based counseling techniques during their implementation. Of course this is motivated by the existence of a phenomenon that occurs in every individual, that surely every human being experiences excessive fear or feels anxiety when he sees an object that can harm him. Anxiety is not considered normal when individuals feel anxiety about an object where other people are not afraid of that object. The purpose of this research is to assist individuals in dealing with anxiety that occurs in them, by using techniques and carrying out relaxation stages and then intervened with dhikr to help reduce anxiety problems felt by individuals. The data source used in this study is secondary data, this data source is obtained from journals or articles related to systematic desensitization techniques. The results of this study are researchers evaluating and integrating this systematic desensitization technique into one of the Islamic-based counseling approaches.